Insight-HXMT observations of jet-like corona in a black hole X-ray binary MAXI J1820+070 - You, Bei; Li, Chengzhe; Wang, Wei; Zhang, Shu; Ge, Mingyu; Luo, Chong; Liu, Bifang; Yuan, Weimin; Dai, Zigao; Jin, Chichuan; Czerny, Bozena; Wu, Qingwen; et al. (Nature communications, 2021)
A black hole X-ray binary produces hard X-ray radiation from its corona and disk when the accreting matter heats up. During an outburst, the disk and corona co-evolves with each other. However, such an evolution is still unclear in both its geometry and dynamics. Here we report the unusual decrease of the reflection fraction in MAXI J1820+070, which is the ratio of the coronal intensity illuminating the disk to the coronal intensity reaching the observer, as the corona is observed to contrast during the decay phase. We postulate a jet-like corona model, in which the corona can be understood as a standing shock where the material flowing through. In this dynamical scenario, the decrease of the reflection fraction is a signature of the corona’s bulk velocity. Our findings suggest that as the corona is observed to get closer to the black hole, the coronal material might be outflowing faster. Evolution of accretion disk and corona during outbursts in black hole binary systems is still unclear. Here, the authors show spectral analysis of MAXI J1820+070 and propose a scenario of a dynamical corona to explain the evolution of the reflection fraction observed by Insight-HXMT.